Efektifitas Konseling Behavioristik Dengan Teknik Desensitisasi Untuk Mengurangi Nomophobia Di Dalam Ruang Kelas - Venazmi Livia Buamona; Suryani Hi Umar; Nursin M Sapil; Happy Karlina M (Syntax Literate, 2023)
The condition of adolescents in the midst of technological developments has a negative impact, in addition to the positive benefits felt by adolescents. When they are familiar with smartphones, they then forget the conditions around them, causing addiction to these smartphones. The phenomenon is known as Nomophobia, which is a psychological disorder that is influenced by a person's dependence on gadgets. Teenagers who are included in this phenomenon, need counseling steps. The purpose of this study is to describe effective counseling steps using behavioristic methods with desensitization techniques to reduce nomophobic behavior. The researcher used a qualitative method with a literature review approach, resulting in the results that the steps in implementing behavioristic counseling with systematic desensitization techniques on nomophobia behavior can be carried out through 1) case diagnosis analysis, 2) behavioristic counseling treatment, 3) providing follow-up as an effort to follow up on the problem of nomophobia in students. Regarding the effectiveness of the implementation of counseling on the behavior of students with nomophobia, the researchers found that behavioristic counseling with desensitization techniques was classified as very structured, because it included several instruments namely 1) need assessment or fostering good relations, 2) goal setting, 3) early stages of implementation counseling techniques (treatment), 4) identify situations that give rise to counselee's tension and anxiety and 5) feed back or feedback. So that behavioristic counseling techniques as a step to reduce nomophobia can be carried out by counselors to improve their behavior patterns by desensitizing or pleasant relaxation movements to reduce students' anxiety about their smartphones while studying. On the other hand, this effectiveness also helps to reduce the frequency of students using smartphones by controlling or self-management, as well as parental control over children